Digital Comics for Differentiated Learning: A Strategy to Enhance Elementary Reading Skills - Hidayat, Nanang Rohmat; Roemintoyo, Roemintoyo; Sutimin, Leo Agung (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The Covid-19 pandemic has had a profound impact on the education sector, particularly in rural areas, and this effect continues to be felt. The transition to online learning technologies during this period was not effectively implemented. This situation underscores the necessity for accessible and effective media literacy resources to support reading skills. This study aims to enhance the reading abilities of elementary school students through the development of differentiated digital comics (KODI), specifically designed to cater to diverse learning needs. Employing a Research and Development (R&D) approach based on the ADDIE model, the study involved one media expert, one content expert, and 30 fourth-grade students. Data collection was conducted through observations, interviews, and questionnaires, which were analyzed using both qualitative and quantitative methods. The needs analysis revealed significant variations in students' reading abilities and preferences, highlighting the urgency for differentiated media. Expert validation indicated that KODI met the eligibility criteria, achieving an average validity score of 84.9%, categorizing it as